Efforts to Manage Children's Emotional Intelligence Through the Implementation of Storytelling Methods - Arifin, Zainul; Rahmi, Azvi; Dewita, Rina; Sarianto, Debi (Institute of Research and Community Service STAI Yayasan Tarbiyah Islamiyah Kota Padang, 2024)
In April 2025, it was found that children's emotional intelligence was still not well managed, because there were still many students who lacked focus, disturbed friends and other actions in the teaching and learning process. Children's emotional intelligence needs to be managed, therefore learning must be interesting and fun. One way to manage children's emotional intelligence is through the storytelling method. This study aims to (1) Identify factors that influence children's emotional intelligence at Ammatullah Kuranji Islamic Kindergarten Padang in the 2024-2025 Academic Year; and (2) Develop strategies for managing children's emotional intelligence through the storytelling method at Ammatullah Kuranji Islamic Kindergarten Padang in the 2024-2025 Academic Year. This study uses a quantitative research method, the subjects in this study were students of Ammatullah Kuranji Islamic Kindergarten Padang. The number of students who became subjects was 30 children. This research was collaborative between class teachers, the principal and the author. The results of the study showed that there was an increase in children's emotional intelligence management through storytelling, with a 34% increase in pre-test emotional intelligence and an 86.7% increase in post-test emotional intelligence. The conclusion of this study is that children's emotional intelligence can be managed through storytelling.